Analysis of Business Strategies to Increase Competitiveness During the Covid-19 Pandemic in the Aco Interior Design in Bandar Lampung - Cartatika, Amanda; Ali Alam, Iskandar (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study is to find out Business Strategies to increase competitiveness during the pandemic, increase interior development as it is today, so that more and more competitors in the interior sector result in Aco Interior. Regarding product development during the covid-19 pandemic, sales tend to decline, on average - reaching -2.88%, this condition may be the strategy used is not right. The design of this research uses qualitative research using observation techniques, interviews, with a population and a sample of 3 competitors with aco interior position as a challenge. This research can be said as several points in writing, namely, from SWOT analysis, IFAS EFAS calculations. The results of the analysis of the SWOT analysis of the Cartesian diagram show that the interior aco is in the growth quadrant I (SO) position, so the strategy that is used is to take advantage of existing opportunities. With that Aco Interior is able to create different products that have characteristics that do not exist in other interior competitors and maintain the quality of existing ones.